2010
DOI: 10.4103/0973-1482.73336
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective potential of mint: A brief review

Abstract: Radiation is an important modality in cancer treatment and estimates are that between one third and one half of all patients will require ionizing irradiation therapy during some point in their clinical management. However, the radiation-induced damage to the normal tissues restricts the therapeutic doses of radiation that can be delivered to tumors and thereby limits the effectiveness of the treatment. The use of chemical compounds (radioprotectors) represents an obvious strategy to improve the therapeutic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 43 publications
(78 reference statements)
2
44
0
Order By: Relevance
“…It is rich in polyphenols like menthoside, rutin, tilianine and luteolin. The essential oil of mint contains menthol, menthone, methyl esters, carvone, limonene and mycrene (Baliga and Rao 2010). P. betle is a common vine belonging to the family piperaceae.…”
Section: Introductionmentioning
confidence: 99%
“…It is rich in polyphenols like menthoside, rutin, tilianine and luteolin. The essential oil of mint contains menthol, menthone, methyl esters, carvone, limonene and mycrene (Baliga and Rao 2010). P. betle is a common vine belonging to the family piperaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Peppermint has numerous pharmacological, cosmetic and alimental applications due to its ability to produce terpene and terpenoid compounds. Ba- [114] reported that mint was protected mice against the γ-radiationinduced sickness and mortality. The radioprotective effects are possibly due to free radical scavenging, antioxidant, metal chelating, anti-inflammatory, antimutagenic, and enhancement of the DNA repair processes.…”
Section: Peppermint (Mentha Piperita)mentioning
confidence: 99%
“…The essential oils of Mentha longifolia L. (M. longifolia) have been extensively investigated, as evident in a large number of studies focusing on their antiviral, antimicrobial, antifungal [10][11][12], antibiofilm formation [13][14][15], radioprotective [16,17], antioedema, analgesic and antioxidant properties [13].…”
Section: Introductionmentioning
confidence: 99%